2016
DOI: 10.3390/app6070187
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Single Electron Devices: Charge Offset Drift

Abstract: Single electron devices (SEDs) afford the opportunity to isolate and manipulate individual electrons. This ability imbues SEDs with potential applications in a wide array of areas from metrology (current and capacitance) to quantum information. Success in each application ultimately requires exceptional performance, uniformity, and stability from SEDs which is currently unavailable. In this review, we discuss a time instability of SEDs that occurs at low frequency ( 1 Hz) called charge offset drift. We review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 55 publications
1
18
0
Order By: Relevance
“…SETs are considered to be the world's most sensitive electrometers, with the capability of detecting the motion of individual electrons or charge instabilities [13][14][15][16][17] . The same sensitivity that enables exquisite readout of a target qubit is also susceptible to any other charge motion within the local environment, e.g., unintentional charge defects.…”
Section: Reduction Of Charge Offset Drift Using Plasma Oxidized Alumimentioning
confidence: 99%
See 1 more Smart Citation
“…SETs are considered to be the world's most sensitive electrometers, with the capability of detecting the motion of individual electrons or charge instabilities [13][14][15][16][17] . The same sensitivity that enables exquisite readout of a target qubit is also susceptible to any other charge motion within the local environment, e.g., unintentional charge defects.…”
Section: Reduction Of Charge Offset Drift Using Plasma Oxidized Alumimentioning
confidence: 99%
“…Extensive prior work examining the charge offset stability of various materials showed that metallic SETs incorporating AlO x tunnel barriers demonstrate severe time instability-random, time-dependent phase fluctuations in the control curve [13][14][15][16][17][18] . These large, abrupt changes are attributed to two-level system (TLS) defects associated with amorphous AlO x , consistent with similar findings from TLS spectroscopy studies in the context of superconducting qubits [19][20][21] .…”
Section: Reduction Of Charge Offset Drift Using Plasma Oxidized Alumimentioning
confidence: 99%
“…These have been shown to occur due to charge offsets fluctuating over time in glassy media and their intrinsic two-level systems (TLS). 15,16 Finally, unintentional quantum dots, charge traps, or charge defects can influence a desired quantum state. This class of effects can manifest when the scale of the wave function of the charge carriers involved is equal to the scale of (unintended) features or variations in the structure.…”
mentioning
confidence: 99%
“…These have been shown to occur due to charge offsets fluctuating over time in glassy media and their intrinsic twolevel systems (TLS). 34,70 Finally, unintentional quantum dots, charge traps, or charge defects can influence a desired quantum state. This class of effects can manifest when the scale of the wavefunction of the charge carriers involved is equal to the scale of (unintended) features or variations in the structure.…”
Section: Quantum Dot Heterostructuresmentioning
confidence: 99%
“…168 One of the ways to extract the charge offset is by taking the trace of a number of Coulomb oscillations as a function of gate voltage V g . The oscillations are modelled as a function of regularly interspaced peaks and fitted using the following general formula: 70 I D (V g ) = A 0 + A sin (2πV g /∆V g +Q 0 (t )/e) + BV g (7.1) with A 0 the base current, A the amplitude of the peaks, B accounts for a linear increase of background current. The charge offset is given as Q 0 = phase ∆V g e, with ∆V g the periodicity of the Coulomb oscillations.…”
Section: Confinementmentioning
confidence: 99%